Shari’a heterogeneity of Indian Islamic Waqf Law and AAOIFI Standard: comparative study in light of classical rulings - Hassan, Rusni; Siddiqi, Yousof Azim; Ali, Jawwad (2020)
The establishment of the institution of Waqf, or Islamic endowment, was evident from the early days of Islam. Hence, the companions of the Prophet (PBUH) had established Waqf for their family members or needy people. Over a period of time, Waqf played a vital role in Islamic history by serving sectors like health, education, and social welfare. By the introduction of Islam in India, the institution of Waqf spread in Delhi and then to other parts. Governance of these Waqf bodies were directly managed by the royal court of the Muslim emperor. After the fall of the Mughal Empire, some acts were enacted by the British empire. Post-independence of India, new laws and acts related to Waqf were enacted, but Shariah observation was not the core theme of these acts. Muslim Personal Law Board (India) suggested a Waqf law for Muslims based on fiqh rulings. This study compares the rulings of Islamic Waqf Law against AAOIFI’s Shari’ah Standard on Waqf (issued in 2019). The methodology is qualitative. The study is divided into a) Introduction, b) Literature Review, c) Analysis and d) Conclusion and Recommendation. The study found five instances of Shari’ah heterogeneity where IIWL has less favourable implications, besides 22 rulings where IIWL has no stand. The study recommends revising IIWL to ensure the growth of Waqf and longer sustainability